A Heritage School for Young Korean American Students - Younglong Kim; Katherine Curry; Ashlyn Fiegener; Jentre Olsen; Dominic Egure (Journal of Research in Education and Pedagogy, 2025)
The purpose of this study is to understand how a local heritage school in a rural area supports young Korean American students’ learning of heritage language towards the maintenance of cultural identity through the lens of Self-Determination Theory. This study addresses three research questions: How has this Korean school nurtured student motivation for learning their heritage language and culture through competence support? How has this Korean school nurtured student motivation for learning their heritage language and culture through relatedness support? And how has this Korean school nurtured student motivation for learning their heritage language and culture through autonomy support? This study was guided by a qualitative case study following Merriam and Tisdell (2016) to produce a holistic description through multiple forms of data collection including interviews, observations, and document analysis. The findings provide the context of the heritage language learning experiences of young Asian American students in the United States, addressing their unique challenges. Findings also highlight that participation in the heritage school created a bridge, connecting Korean and American cultures with community, among a minority population in a rural area; built students’ self-identity; and enhanced the competence of participants’ mother-tongue-language as well as their cultural literacy. This study emphasizes the significance of creating environments where young Asian American students feel a sense of belonging to aid the development of these competencies, especially in rural areas.